A Review on Occlusal Plane Analysis in Edentulous Patients - Lakshmi.S1 , Sanjna Nayar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The Purpose of the present review was to determine the occlusal plane in edentulous patients.Objective : Occlusal plane orientation is an important factor in the construction of a complete denture.Occlusal plane could be oriented using landmarks in the maxillary arch as well as the mandibular arch .Many methods have been used to establish the occlusal plane in complete dentures , but no method seemsto be fully acceptable. So it is always challenging for the prosthodontist to restore the existing occlusalcondition with a suitable prosthesis.Materials and Methods : : An electronic search engine without time/ language restrictions was taken fromGoogle Scholar .Conclusion: This article reviews different techniques to determine and correct occlusal plane. HIP wasparallel to the occlusal plane , Ala-tragal line passing through lower part of the ala of the nose to inferiorposition of the tragus was relatively parallel to maxillary residual ridge. Therefore, this may be a viablereference in complete denture prosthodontics.